2011
DOI: 10.5194/hess-15-931-2011
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in water resources availability in the Okavango River basin as a result of climate change

Abstract: Abstract. This paper assesses the hydrological response to scenarios of climate change in the Okavango River catchment in Southern Africa. Climate scenarios are constructed representing different changes in global mean temperature from an ensemble of 7 climate models assessed in the IPCC AR4. The results show a substantial change in mean flow associated with a global warming of 2 • C. However, there is considerable uncertainty in the sign and magnitude of the projected changes between different climate models,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 23 publications
3
75
0
Order By: Relevance
“…Although this is initially surprising (the CRU database contains more station data points than UDel), these results follow previous findings (Hughes et al, 2011). One possible reason for this apparent contradiction is that whilst the CRU dataset intermittently captures more detail in regional precipitation than UDel, not all of this regional detail is relevant for the Mekong River Basin (i.e.…”
Section: Calibration and Validation Of The Slurp Hydrological Modelsupporting
confidence: 61%
See 1 more Smart Citation
“…Although this is initially surprising (the CRU database contains more station data points than UDel), these results follow previous findings (Hughes et al, 2011). One possible reason for this apparent contradiction is that whilst the CRU dataset intermittently captures more detail in regional precipitation than UDel, not all of this regional detail is relevant for the Mekong River Basin (i.e.…”
Section: Calibration and Validation Of The Slurp Hydrological Modelsupporting
confidence: 61%
“…In common with other modelling studies undertaken within the QUEST-GSI project (e.g. Hughes et al, 2011;Kingston and Taylor, 2010), a baseline period of 1961-1990 was used for calibration, with the remaining 1991-1998 data used for validation. The input climate data were derived from the monthly CRU TS 3.0 dataset disaggregated to daily resolution (as described in Todd et al, 2011), rather than the relatively sparse GSOD daily station based dataset.…”
Section: The Slurp Hydrological Modelmentioning
confidence: 99%
“…This partly corresponds to the observation pointed out by several authors , Hughes et al 2011, Nóbrega et al 2011) that the mean annual runoff can mask considerably greater seasonal variations which are of high importance to water management.…”
Section: Discussionmentioning
confidence: 92%
“…As in this study, a large body of existing hydrological impact studies also identified GCM structure as the dominant source of uncertainty (e.g. Kingston and Taylor, 2010;Hughes et al, 2011;Teng et al, 2012;Thompson et al, 2014). It should be noted that the four GCMs constitute a subset of a total of 12 GCMs which had been previously selected by NIWA on the basis of a performance assessment for the South Pacific region (Ministry for the Environment, 2008).…”
Section: Discussionmentioning
confidence: 99%